2020
DOI: 10.3390/ijms21062179
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Endothelial TRPV4 Channels Alters the Dynamic Ca2+ Signaling Profile in Mouse Carotid Arteries

Abstract: Transient receptor potential vanilloid 4 channels (TRPV4) are pivotal regulators of vascular homeostasis. Altered TRPV4 signaling has recently been implicated in various cardiovascular diseases, including hypertension and atherosclerosis. These versatile nonselective cation channels increase endothelial Ca2+ influx in response to various stimuli including shear stress and G protein-coupled receptor (GPCR) activation. Recent findings suggest TRPV4 channels produce localized Ca2+ transients at the endothelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…It has been demonstrated that TRPV4 channels give rise to Ca 2+ transients in the plasma membranes of endothelial cells that lead to the recruitment of other downstream effectors that result in a magnified Ca 2+ signaling [83]. McFarland and collaborators used an endothelium-specific trpv4 −/− mouse model (ecTRPV4 −/− ) where the channel was specifically knocked down in keratinocytes, to newly show that the artery endothelium from the intact arterial intima of these animals produces larger Ca 2+ events (via release from internal stores), as compared to the wild-type counterparts but these mutant mice also display deficiencies in "small events", meaning that TRPV4 channels generate focal Ca 2+ transients and are essential for vascular homeostasis [84].…”
Section: Trpv4 and The Vascular Endotheliummentioning
confidence: 99%
“…It has been demonstrated that TRPV4 channels give rise to Ca 2+ transients in the plasma membranes of endothelial cells that lead to the recruitment of other downstream effectors that result in a magnified Ca 2+ signaling [83]. McFarland and collaborators used an endothelium-specific trpv4 −/− mouse model (ecTRPV4 −/− ) where the channel was specifically knocked down in keratinocytes, to newly show that the artery endothelium from the intact arterial intima of these animals produces larger Ca 2+ events (via release from internal stores), as compared to the wild-type counterparts but these mutant mice also display deficiencies in "small events", meaning that TRPV4 channels generate focal Ca 2+ transients and are essential for vascular homeostasis [84].…”
Section: Trpv4 and The Vascular Endotheliummentioning
confidence: 99%
“…One of the drugs that proved effectiveness in alleviating headache is sumatriptan that inhibits TRPV1 channel [ 71 ]. Also, it was found that the use of civamide [an intranasal TRPV1 agonist] reduced the frequency of headache attacks in patients [ 72 ]. Furthermore, TRPV4 mRNA is expressed in TG neurons compared to the minimal expression of TRPM8 mRNA [ 70 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the endothelial cells of carotid artery, TRPV4 loss of function caused problems in blood pressure and vascular tone [ 99 ]. In another study, it was demonstrated that TRPV4 loss of function induced Ca 2+ release from internal stores, thus affecting vascular homeostasis [ 72 ]. The relation between TRP channels and Ca 2+ ions that are needed for the viral activities suggests that TRP channels can be targeted in COVID-19 disease.…”
Section: Resultsmentioning
confidence: 99%
“…TRPV4 cation channels elicit focal Ca 2+ influx events at the plasma membrane (Ca 2+ sparklets), allowing for localized signal targeting and providing a trigger for larger Ca 2+ -induced Ca 2+ release events (i.e., from the endoplasmic reticulum) ( Sullivan et al, 2012 ; Lin et al, 2015 ; Heathcote et al, 2019 ; McFarland et al, 2020 ). Growing evidence supports involvement of these channels in shear stress and agonist-mediated endothelial signaling, and changes in TRPV4 signaling are linked to disease states including hypertension, diabetes and pulmonary edema ( Hartmannsgruber et al, 2007 ; Mendoza et al, 2010 ; Sonkusare et al, 2012 ; Ma et al, 2013 ; Monaghan et al, 2015 ; Zhang et al, 2018 ; Daneva et al, 2021 ; Rajan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%